Does touch massage facilitate recovery after stroke? A study protocol of a randomized controlled trial. Issue 1 (December 2015) - Lämås, Kristina; Häger, Charlotte; Lindgren, Lenita; Wester, Per; Brulin, Christine
Abstract Background Despite high quality stroke care, decreased sensorimotor function, anxiety and pain often remain one year after stroke which can lead to impaired health and dependence, as well as higher healthcare costs. Touch massage (TM) has been proven to decrease anxiety and pain, and improve quality of health in other conditions of reduced health, where reduced anxiety seems to be the most pronounced benefit. Thus there are reasons to believe that TM may also reduce anxiety and pain, and improve quality of life after stroke. Further, several studies indicate that somatosensory stimulation can increase sensorimotor function, and it seems feasible to believe that TM could increase independence after stroke. In this study we will evaluate effects of TM after stroke compared to sham treatment. Methods This is a prospective randomized open-labelled control trial with blinded evaluation (PROBE-design). Fifty patients with stroke admitted to stroke units will be randomized (1:1) to either a TM intervention or a non-active transcutaneous electrical nerve stimulation (non-TENS) control group. Ten sessions of 30 min treatments (TM or control) will be administered during two weeks. Assessment of status according to the International Classification of Functioning, Disability and Health (ICF), including body function, activity, and participation. Assessment of body function will include anxiety, pain, and stress response (heart rate variability and salivary cortisol), where anxiety is the primary outcome. Activity will be assessed by means of sensorimotor function and disability, and participation by means of health-related quality of life. Assessments will be made at baseline, after one week of treatment, after two weeks of treatment, and finally a follow-up after two months. The trial has been approved by the Regional Ethical Review Board. Discussion TM seems to decrease anxiety and pain, increase health-related quality of life, and improve sensorimotor functions after stroke, but the field is largely unexplored. Considering the documented pleasant effects of massage in general, absence of reported adverse effects, and potential effects in relation to stroke, it is essential to evaluate effects of TM during the sub-acute phase after stroke. The results of this project will hopefully provide important knowledge for evidence-based care. Trial registration ClinicalTrials.gov:NTC01883947